Model Komunikasi Pemberdayaan Dosen dalam Meningkatkan Akreditasi Program Studi Menuju Unggul di PTKIN (Studi di UIN Syahad Padangsidimpuan, UMTS, IPTS, dan STAIN Madina) - Nurfitriani M. Siregar; Anas Habibi Ritonga; Gina Sonya Pane; Ismi Alawiah; Zakia Pane (IAIN Padangsidimpuan, 2025)
This study aims to analyze the communication model for empowering lecturers in efforts to improve study program accreditation toward achieving excellent status in State Islamic Higher Education Institutions (PTKIN) and Private Higher Education Institutions (PTS) in North Sumatra. The research focuses on UIN Syekh Ali Hasan Ahmad Addary (SYAHADA) Padangsidimpuan, Universitas Muhammadiyah Tapanuli Selatan (UMTS), Institut Pendidikan Tapanuli Selatan (IPTS), and STAIN Madina. Using a qualitative approach and case study method, this study examines the dynamics of communication within these institutions. The findings reveal that an effective communication model involves collaboration, transparency, and the provision of constructive feedback. Institutions that successfully empower their lecturers emphasize participatory communication strategies that allow lecturers to be actively involved in decision-making and planning processes related to accreditation improvements. Additionally, the integration of information technology-based communication is identified as a critical factor in facilitating coordination and monitoring of accreditation progress. This study underscores the importance of creating an environment that fosters open dialogue and trust between academic leaders and lecturers. It offers practical recommendations for higher education administrators to adopt participatory communication models that support lecturer empowerment. By doing so, institutions can enhance their capacity to achieve superior accreditation outcomes and improve overall academic quality.